Effectiveness of Multicomponent Elderly Exercise on Balance and Fall Risk: SKILAS-based Screening in West Lombok Elderly Schools - Supinganto, Agus; Mulyoto, Raufina Riandhani; Metri, Ni Ketut; Karang, Ni Nyoman Melani; Adyasputri, A A I Ayesa Febrinia; Hidayatullah, M. Syarif (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2026)
Background: Falls are a major public health problem among older adults, leading to injuries, disability, and loss of independence. Community-based exercise programs are recommended as a preventive strategy. Objective: This study aimed to evaluate the effectiveness of a 4-week multicomponent elderly exercise program on balance and fall risk among Elderly School participants in West Lombok, Indonesia. Methods: A quasi-experimental one-group pretest–posttest design was conducted in February 2025 in Gunungsari, Mambalan Village. Sixty older adults aged ≥60 years were recruited using purposive sampling. Balance and fall risk were assessed using the Berg Balance Scale (BBS) and Timed Up and Go (TUG), while functional status was recorded using the SKILAS form. The intervention consisted of multicomponent exercise sessions conducted twice weekly for four weeks (eight sessions). Paired t-test or Wilcoxon signed-rank test was applied for continuous variables, and McNemar or chi-square test for categorical outcomes. Statistical significance was set at α = 0.05, with effect sizes and 95% confidence intervals (CI) reported. Results: Mean BBS scores significantly increased from 38.5 (95% CI: 37.42–39.58) at baseline to 45.7 (95% CI: 44.72–46.68) post-intervention, indicating a mean improvement of 7.2 points (p < 0.001; Cohen’s d ≈ 0.72). The proportion of participants at risk of falls decreased from 40% (24/60; 95% CI: 28.6–52.6%) to 18% (10/60; 95% CI: 9.3–28.0%), representing an absolute reduction of 22 percentage points (p = 0.002). Conclusion: A 4-week multicomponent elderly exercise program significantly improved balance and reduced fall risk among older adults. This intervention is recommended for routine implementation in Elderly Schools and primary healthcare settings as a practical and effective fall-prevention strategy.